2008
DOI: 10.1089/pho.2008.2225
|View full text |Cite
|
Sign up to set email alerts
|

Severity of Oral Mucositis in Patients Undergoing Hematopoietic Cell Transplantation and an Oral Laser Phototherapy Protocol: A Survey of 30 Patients

Abstract: The low grades of OM observed in this survey show the beneficial effects of laser phototherapy, but randomized clinical trials are necessary to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 33 publications
1
9
0
7
Order By: Relevance
“…The use of therapeutic laser in the present study showed positive outcomes and the efficacy of laser to prevent and treat OM in patients subjected to HSCT, chemotherapy and radiotherapy, in accordance with data found in the literature (8,(11)(12)(13)(14)(15)(16)18,20) and the results were similar to those obtained by Antunes et al (12). The outcomes of the present study add to the evidence that therapeutic laser can be an effective option for the prevention and treatment of OM in patients subjected to HSCT with the absence of adverse effects or discomfort, as suggested by other authors (11,13).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The use of therapeutic laser in the present study showed positive outcomes and the efficacy of laser to prevent and treat OM in patients subjected to HSCT, chemotherapy and radiotherapy, in accordance with data found in the literature (8,(11)(12)(13)(14)(15)(16)18,20) and the results were similar to those obtained by Antunes et al (12). The outcomes of the present study add to the evidence that therapeutic laser can be an effective option for the prevention and treatment of OM in patients subjected to HSCT with the absence of adverse effects or discomfort, as suggested by other authors (11,13).…”
Section: Discussionsupporting
confidence: 92%
“…nm (9), while current studies use several types of diodes such as the InGaAIP laser of 660 nm (18), the InGaAlP laser of 685 nm (14) and 660 nm (12), the GaAlAs laser of 830 nm (16). Eduardo et al (18) reported the use of a InGaAIP laser (660 nm) with 40 mW and energy density of 4 J/ cm 2 (for prevention of ulceration) or 6 J/cm 2 (for treatment of confirmed ulcerations) in 30 patients undergoing autologous (63.3%) or allogeneic (36.7%) HSCT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6] Studies on the effects of LPT, either alone or in combination with other therapies, conducted in patients with immunosuppression, have shown that LPT promotes a reduction in pain intensity and mucositis severity, acceleration of wound healing, analgesic effects and an increase in the salivary flow rate, with no side effects. [3][4][7][8] Studies involving animal models allow a better understanding of the pathobiology of mucositis and a more in-depth evaluation of the effects of therapies for the prevention and treatment of this disease. The model for induced mucositis in hamsters was initially proposed by Sonis et al 9 and has proven useful in preclinical studies on new treatment options for mucositis.…”
Section: Introductionmentioning
confidence: 99%
“…Les lasers hélium-néon (He/Ne, longueur d'ondes 632,8 nm) et à diode (longueur d'ondes 650 à 905 nm) sont les plus fréquemment rapportés dans ces indications, comme le laser InGaAIP de 660 nm [17] et 685 nm [18] et le laser GaAlAs de 830 nm [19]. Bien que l'intérêt du laser dans les mucites soit maintenant incontestable, la question de la puissance utilisée et du protocole fait actuellement débat.…”
Section: Commentairesunclassified